Działalność pełnomocnika Marszałka Województwa Dolnośląskiego na rzecz współpracy z uczelniami wyższymi .......... 63 - Czapiewski, Edward (Samorząd terytorialny na Dolnym Śląsku: Sprawy, dylematy i wyzwania, 2025)
THE ACTIVITIES OF THE PLENIPOTENTIARY OF THE MARSHAL OF THE LOWER SILESIAN VOIVODESHIPFOR COOPERATION WITH HIGHER EDUCATION INSTITUTIONSThe author examines the legal framework governing his role as the Plenipotentiary of the Marshal of the Lower Silesian Voivodeship for cooperation with higher education institutions. He emphasises both the broad scope of potential activities and the limitations resulting from the lack of financial instruments to support specific initiatives. The article outlines the plenipotentiary’s responsibilities and presents selected initiatives undertaken within formal competences as well as through independent cooperation with relevant stakeholders. In conclusion, the author advocates a shift in the character of the role—from lobbying for individual initiatives towards supporting strategic and conceptual work—particularly in view of the anticipated future merger of voivodeship offices and marshal’s offices, which could enhance public administration efficiency at the regional level.